2020
DOI: 10.1097/meg.0000000000001830
|View full text |Cite
|
Sign up to set email alerts
|

Chromium picolinate balances the metabolic and clinical markers in nonalcoholic fatty liver disease: a randomized, double-blind, placebo-controlled trial

Abstract: Objective Nonalcoholic fatty liver disease (NAFLD) is a complicated disease and is considered as a severe global health problem affecting 30% of adults worldwide. The present study aimed to evaluate changes in oxidative stress, adipokines, liver enzyme, and body composition following treatment with chromium picolinate (CrPic) among patients with NAFLD. Participants and methods The current randomized, double-blind, placebo-controlled study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 60 publications
(80 reference statements)
1
13
0
Order By: Relevance
“…In conformity with our findings, the results of a recent pilot RCT performed by Kooshki et al (2020) showed that there were no meaningful differences in nutritional factors including energy intake and serum levels of albumin and pre‐albumin by nano‐curcumin supplementation. Also, the length of ICU stay did not significantly change between the nano‐curcumin and placebo groups.…”
Section: Discussionsupporting
confidence: 93%
“…In conformity with our findings, the results of a recent pilot RCT performed by Kooshki et al (2020) showed that there were no meaningful differences in nutritional factors including energy intake and serum levels of albumin and pre‐albumin by nano‐curcumin supplementation. Also, the length of ICU stay did not significantly change between the nano‐curcumin and placebo groups.…”
Section: Discussionsupporting
confidence: 93%
“…Nonalcoholic fatty liver disease (NAFLD) is a serious and growing medical problem that manifest by the presence of fat in more than 5% of the hepatocytes. NAFLD encompasses a broad spectrum of liver diseases from simple steatosis to nonalcoholic steatohepatitis with further progression to fibrosis, cirrhosis, and hepatocellular carcinoma [1]. The prevalence data reflect that the NAFLD affects about 8–45% of the adult population in the world [2] and currently, prevalence of NAFLD was reported approximately 33.9% in Iran [3].…”
Section: Introductionmentioning
confidence: 99%
“…e "two-hit" model was revised in 2010 with a "multiple parallel hit" model. In the revised model, fat accumulation in the liver and IR, multiple simultaneous changes lead to an imbalance between antilipotoxic protection systems in the liver and the production of free radicals, endoplasmic stress, decrease in mitochondrial content, disruption of mitochondrial Boxidation, OS, overproduction of reactive nitrogen and oxygen species (RNS/ROS), and death of liver cells [8][9][10]. Even though obesity, especially central obesity, is a wellknown risk factor for NAFLD, it has also been reported in slim people (BMI <30 kg/m2) [11].…”
Section: Introductionmentioning
confidence: 99%